Influence of thiol connections on maintenance of glutathione in blood of judoists of high qualification - Musakhanov Z.A.; Zemtsova I.I.; Stankevich L.G.; Dolgopolova V.I. (Pedagogìka, Psihologìâ ta Mediko-bìologìčnì Problemi Fìzičnogo Vihovannâ ì Sportu, 2012)
A question is considered about a place in the exchange of matters of glutathione, him general amount and picked up a thread form in blood of sportsmen. 18 sportsmen (eyelids - 18-24) which are on the stage of direct preparation to the competitions took part in research. Certainly, that before a basic experiment blood of sportsmen contained a few of general glutathione and him the picked up a thread form with antioxidant properties. For the correction of content of glutathione in blood were drawn on two metabolic complexes. The first complex contained amino acid-predecessors of glutathione. Second are predecessors of phosphocreatine. Sportsmen drew on complexes during three weeks. More effective influenced on the level of glutathione at blood of sportsmen of the use of amino acid - predecessors of glutathione. It is set that one of ways of correction of the state of the system of glutathione there is the use of sulfur-containing connections, including thiol antioxidants.